Instagram Filter Bubbles and Young Voters' Political Preferences in West Nusa Tenggara, Indonesia: Case on The 2024 Presidential Election - Satriyadi, Yadi; Arzak, Miftahul; Maulidyawati, Desi (Golden Ratio of Social Science and Education, 2025)
This study aims to understand how the political preferences of young voters in the province of West Nusa Tenggara (NTB), Indonesia, are shaped through exposure to political content on Instagram during the 2024 Presidential and Vice-Presidential elections. The primary focus of this research is the phenomenon of the filter bubble, a condition in which Instagram's algorithm curates content aligned with users' behaviors and preferences, thereby limiting the diversity of political information they receive. Adopting a qualitative methodology with a phenomenological approach, the study involved six young voters who were active Instagram users during the campaign period. The findings reveal that the filter bubble phenomenon occurs in three stages: algorithm formation, algorithmic reinforcement of perception, and attitude construction. The respondents' frequent interactions with political content, such as following candidate accounts, liking, sharing, and filtering information, indirectly reinforced their initial political preferences. Although they perceived themselves as receiving information from various sources, they were within a homogenous and enclosed informational space. These findings underscore the critical importance of digital political literacy, enabling young voters to comprehend how algorithms operate and avoid being trapped in an echo chamber that narrows opportunities for dialogue in a digital democracy.